The Effect of Food Information Quality and Delivery Offline Satisfaction on Attitudinal Loyalty Through Perceived Usefulness Among GoFood Online Food Delivery Service Users in Bandung City - Daffa Surya Pratama; Abdul Ahmad Hafidh Nurmansyah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study examines the effects of Food Information Quality and Delivery Offline Satisfaction on Attitudinal Loyalty, both directly and through Perceived Usefulness, among GoFood users in Bandung City. A quantitative approach was employed through a survey of 146 GoFood users selected using purposive sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed using descriptive statistics, validity and reliability tests, multiple linear regression, and the Sobel z statistic with SPSS version 26. The results show that Food Information Quality and Delivery Offline Satisfaction have positive and significant effects on Perceived Usefulness. Food Information Quality, Delivery Offline Satisfaction, and Perceived Usefulness also have positive and significant effects on Attitudinal Loyalty. Delivery Offline Satisfaction is the strongest direct predictor of Attitudinal Loyalty, with a standardized beta of 0.437. The model explains 49.7% of the variance in Perceived Usefulness and 75.4% of the variance in Attitudinal Loyalty. The Sobel z statistic confirms that Perceived Usefulness significantly mediates the effects of Food Information Quality and Delivery Offline Satisfaction on Attitudinal Loyalty. These findings highlight the importance of integrating digital information quality and offline delivery experience to strengthen perceived usefulness and attitudinal loyalty in online food delivery services.